1998
DOI: 10.1165/ajrcmb.19.3.2999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of LTD4 on Human Airway Smooth Muscle Cell Proliferation, Matrix Expression, and Contraction In Vitro: Differential Sensitivity to Cysteinyl Leukotriene Receptor Antagonists

Abstract: The cysteinyl leukotrienes (CysLTs) mimic many of the features of asthma and are implicated in its pathophysiology. Little, however, is known about the effects of the CysLTs on airways remodeling. In this study the effects of leukotriene D4 (LTD4) on human airway smooth muscle (HASM) cell proliferation and expression of extracellular matrix proteins were investigated. LTD4 (0.1-10 microM) alone had no effect on DNA synthesis in HASM. LTD4, however, markedly augmented proliferation induced by the mitogen, epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
151
0
4

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(163 citation statements)
references
References 36 publications
8
151
0
4
Order By: Relevance
“…Recently, Panettieri et al (40) reported that LTD 4 augments proliferation of human airway smooth muscle induced by epidermal growth factor (EGF). The precise mechanism underlying this synergy is unknown, but can be explained by convergence between LTD 4 signals via a G proteincoupled receptor and EGF signals via an EGFR tyrosine kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Panettieri et al (40) reported that LTD 4 augments proliferation of human airway smooth muscle induced by epidermal growth factor (EGF). The precise mechanism underlying this synergy is unknown, but can be explained by convergence between LTD 4 signals via a G proteincoupled receptor and EGF signals via an EGFR tyrosine kinase.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine stimulates proliferation via activation of c-fos [49], and ET-1 induced proliferation via the stimulation of extracellularregulated kinase microtubule associated protein kinase pathway [50]. More importantly, ET-1 and LTD 4 amplify the proliferative effect of growth factors such as EGF [51,52]. In vivo studies in a Brown-Norway rat model show that sulphidopeptide leukotrienes and ET-1 are both involved in allergen-induced increases in airway smooth muscle proliferation [9,53,54].…”
Section: Mediators Of Airway Smooth Muscle Proliferationmentioning
confidence: 99%
“…However, addition of the leukotrienes LTC 4 and LTB 4 to ASMC cultures did not elicit ASMC proliferation per se. In accordance, it was recently shown that cysteinyl leukotrienes alone did not induce proliferation, but acted in synergy with other factors [36][37][38]. Some studies indicate for a link between eicosanoids and ROS production [14,[22][23][24].…”
Section: Discussionmentioning
confidence: 62%